2009
DOI: 10.1158/0008-5472.can-08-3249
|View full text |Cite|
|
Sign up to set email alerts
|

Zerumbone Abolishes RANKL-Induced NF-κB Activation, Inhibits Osteoclastogenesis, and Suppresses Human Breast Cancer–Induced Bone Loss in Athymic Nude Mice

Abstract: Receptor activator of nuclear factor-KB (NF-KB) ligand (RANKL) has emerged as a major mediator of bone resorption, commonly associated with cancer and other chronic inflammatory diseases. Inhibitors of RANKL signaling thus have potential in preventing bone loss. In the present report, the potential of zerumbone, a sesquiterpene derived from subtropical ginger, to modulate osteoclastogenesis induced by RANKL and breast cancer was examined. We found that zerumbone inhibited RANKL-induced NF-KB activation in mous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 51 publications
3
49
0
Order By: Relevance
“…As the latter is a member in the TNF family of cytokines, agents that can suppress its signaling have been suggested to have therapeutic potential against inflammatory disorders. Aggarwal and co-workers reported that zerumbone can inhibit RANKL-induced NF-kB activation in mouse macrophages (RAW264.7 cells) in a dose-and time-dependent manner [63]. The compound inhibited RANKLinduced IkBa phosphorylation and degradation, IKK activation and osteoclastogenesis.…”
Section: Cem-ss Cells (T-acute Lymphoblastic Leukemia)mentioning
confidence: 97%
See 2 more Smart Citations
“…As the latter is a member in the TNF family of cytokines, agents that can suppress its signaling have been suggested to have therapeutic potential against inflammatory disorders. Aggarwal and co-workers reported that zerumbone can inhibit RANKL-induced NF-kB activation in mouse macrophages (RAW264.7 cells) in a dose-and time-dependent manner [63]. The compound inhibited RANKLinduced IkBa phosphorylation and degradation, IKK activation and osteoclastogenesis.…”
Section: Cem-ss Cells (T-acute Lymphoblastic Leukemia)mentioning
confidence: 97%
“…The process is mediated by osteoclast cells which are generated from hematopoietic cells by the action of several entities including the receptor activator of NF-kB (RANK) and its ligand RANKL [63]. As the latter is a member in the TNF family of cytokines, agents that can suppress its signaling have been suggested to have therapeutic potential against inflammatory disorders.…”
Section: Cem-ss Cells (T-acute Lymphoblastic Leukemia)mentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, 10-gingerol was about 50-fold more potent (IC50 = 12 versus 670 µM, respectively) than 6-gingerol [39]. Ginger and its bioactive molecules are effective in regulatory the degree of colorectal, gastric, ovarian, liver, skin, breast, and prostate cancers [40,[42][43][44][45][46][47]. Kim et al [45] have carried out an experiment in mouse models and administered Zerumbone orally and observed inhibition in a multiplicity of colonic adenocarcinomas through suppression of colonic inflammation in a dose-dependent manner.…”
Section: Anti-cancer Effectsmentioning
confidence: 99%
“…(1,(6)(7)(8)24) Within the positive-feedback loop of metastatic bone disease, initiation of osteoclast activity by interleukin 8 (IL-8), (1,25) parathyroid hormone-related peptide (PTHrP), (4,26,27) and receptor activator of NF-kB ligand (RANKL) (1,28) is implicated. In turn, osteoclast activity releases growth factors in bone that promote tumor proliferation and growth, including transforming growth factor b, (29,30) bone morphogenic proteins, (31,32) and others.…”
Section: Mnu-induced Breast Tumors On Bone Health In Rats (Figs 2 Thmentioning
confidence: 99%